PENGARUH PEMAHAMAN WAWASAN KEBHINEKAAN TERHADAP HASIL BELAJAR MATA KULIAH PENDIDIKAN PANCASILA PADA PROGRAM STUDI PPKn UNIVERSITAS RIAU - Deddy Prianto; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to analyze the influence of students’ understanding of diversity on their learning outcomes at Pancasila and civic education (PPKn) study program of Universitas Riau. Theresearch questions are formulated as follows: how is the students’ understanding of diversity at PPKn study program of Universitas Riau; and how is the student's learning outcomes in Pancasila education courses at PPKn study program of Universitas Riau; and how is the influence of the students’ understanding of diversity on their learning outcomes of Pancasila education courses at PPKn study program of Universitas Riau. This quantitative research was conducted at Universitas Riau from June 2019 to November2019. Participants were 71 PPKn study program students selected using the total sampling method. Data collection techniques in this study were observation, questionnaire and documentation. The data analysis techniques used were a questionnaire instrument analysis in the form of a validity test, a quantitative analysis in the form of a percentage test, a simple linear regression test, a coefficient of determination test and a hypothesis test. This study found that students’ understanding of the diversity isclassified as very good with a percentage of 94.7%. The learning outcomes of the final year students of PPKn study program of Universitas Riau are classified as good, with a percentage of 75.04%. These data indicate that the variable understanding of diversity has a positive effect on the learning outcomes of students at at PPKn study program of Universitas Riau with a magnitude of influence that can be explained by 33.4% of the dependent variable, while the remaining 66.6% (100% -33, 4%) is influenced by other variables which are not included in this study, such as learning resources, learning media and so on. Key Words:Understanding, Insight Into Diversity, Learning Outcomes